The Effectiveness of Socrative Application for Formative Assessment in Teaching Vocabulary at SMPN 16 Kota Tangerang Selatan - Almanar, Muhammad Abduh; Nabila, Hana (Foremost Journal, 2022)
The purpose of this study is to determine whether the Socrative application is effective for teaching vocabulary to students in the eighth grade at SMPN 16 Kota Tangerang Selatan in the academic year 2021/2022. The sampling method was used to divide 64 students into two groups: the controlled group and the experimental group. The design of the study was quasi-experiment, while the instrument was a test with a pre-test and a post-test. The findings indicate that using the Socrative application for formative assessment as a technique for vocabulary learning was effective and appropriate for students.